Distribuição espacial de atributos químicos do solo em área de pastagem e foresta - De Aquino, Renato Eleoterio [UNESP]; Marques Júnior, José [UNESP]; Campos, Milton Cesar Costa; de Oliveira, Ivanildo Amorim [UNESP]; Silva Siqueira, Diego [UNESP] (My University, 2014)
The knowledge on spatial distribution of soil properties by means of geostatistics is important as an indicator for a better soil use and management. This study aimed at evaluating the spatial distribution of soil chemical properties, in a forest and pasture area in Manicoré, Amazonas State, Brazil. Grids with 70.00 m x 70.00 m, with regular spacing of 10.00 m x 10.00 m, totaling 64 points, were established, and then soil samples were collected at the depths of 0.0-0.20 m and 0.40-0.60 m and had their chemical properties determined. Data were analyzed by using descriptive statistics and geostatistics, and the sampling density analysis was based on the coefficient of variation and semivariograms range. The mean and median values were adjusted to the closest values, indicating normal distribution, while the spherical, exponential and gaussian models were adjusted to the soil chemical properties. It was concluded that the geostatistics provided adequate information for understanding the spatial distribution. The forest area showed a higher spatial continuity and the pasture area a lower sampling density. The chemical properties showed differences in the spatial variability, while the range represented better the estimates for sampling density and spacing, in the forest and pasture area.
Spatial distribution of soil chemical properties in pasture and forest area
Keywords: Geostatistics; Sampling density; Spatial variability